(untitled) (Baghdad Science Journal, 2014)
This study was designed to evaluate the effect of major surgery on thyroid hormones and thyrotropin in patient undergoing major lower abdominal surgery. The study included fifty patients scheduled for elective major lower abdominal surgery, the serum levels of T3, T4 and TSH were determined one day preoperatively, intraoperative, one day postoperatively, two days postoperatively, and rT3 was determined one day preoperatively, and one day postoperatively. We observed that the levels of (T3, T4, TSH) increased significantly (P0.05). rT3 increased not significant (P>0.05) in one day postoperatively. It has been proposed these changes due to surgical stress that inhibits peripheral conversion of T4 to T3 by inhibiting peripheral 5’-deiodinase activity, also The absence of pituitary response to changes in serum levels of T3 and T4.According to the results of this study there is a transient abnormality in thyroid function tests in patient undergoing elective major surgery and this abnormality due to surgical stress.